The Epidemiology of Sports-Related Head Injury and Concussion in Water Polo - Blumenfeld, Robert S.; Winsell, Jessica C.; Hicks, James W.; Small, Steven L. (Frontiers in Neurology, 2016)
Purpose: Water polo is a sport with a high degree of physicality and aggressive play. Unlike most contact sports, epidemiological data on the incidence or prevalence of head trauma in water polo have not been gathered, reported, or made publicly available. The purpose of this study was to begin a systematic characterization of the risks of head impact and concussion in men and women who play water polo at various levels. Design: We sent an electronic survey to the 44,000+ members of USA Water Polo, asking questions about concussions, head impacts, and symptoms commonly associated with prior concussion. From over 1500 complete responses, we report summary information on the prevalence of concussions and major head impacts in water polo. Results: We found that 36% of respondents report sustaining a concussion while playing water polo, with an average of 2 concussions reported. The prevalence and number of concussions reported varied across positions, levels, and gender. Most strikingly, we found that goalies are at significantly higher risk for concussion, report a significantly more concussions, and appear to experience a qualitatively different type of head impact compared to other positions. Additionally we found that competition level, gender, and field position are robust predictors of concussion risk. Conclusion: Our findings demonstrate that concussions are not uncommon in water polo players. We conclude that there is need for systematic concussion reporting in water polo and suggest that understanding the risk factors of concussion in water polo will require fully considering differences in the head impact exposure between different field positions, competition levels, sexes and differences in exposure between competition and practice.